A study of verb errors in written English by Chinese ESL students / Kong Yuan Wen - Kong, Yuan Wen (2013)
The research study aims to examine verb errors committed by Chinese ESL students in their written English based on Corder‟s (1981) Taxonomy of errors. Errors are viewed as important elements which are able to represent a learner‟s stages in language learning and reflect their difficulties in the learning process. Studies of error analysis have provided useful guidelines and measurements in improving both teaching methods and materials needed in the learning process. The objectives of this study are to identify and classify verb errors, and to determine the probable causes of such errors. Analysis of the data revealed that the verb errors are due to selection errors, addition errors and omission errors. In addition, the study also highlights verb errors that affected the syntactic function of the sentences. The study reveals that the students‟ language background, language exposure and learning environment affect how they learn the English language. The analysis established that Chinese ESL students are confused by the many verb forms of English and have yet to master the language. This study will serve as a work of reference in the pedagogical field to highlight the problems faced by Chinese ESL learners in learning English verbs, and to suggest remedial works to improve the teaching and learning process.